Pengaruh Model Discovery Learning Berbantuan Video terhadap Hasil Belajar Peserta Didik - Juanda, Refika; Azzahra, Firda; Arif, Khairil; Wati, Fatma (SEMESTA: Journal of Science Education and Teaching, 2025)
This research was motivated by teacher-centered learning, which leads to students not actively participating in the learning process and it affects their learning outcomes. The purpose of this study was to examine the effect of applying the Discovery Learning model on student learning outcomes in science subjects for Grade VII students in junior high school. This study employed a quasi-experimental method, using a non-equivalent control group design. The sampling technique used was purposive sampling, with class VII-3 assigned as the control group using a conventional learning model, and class VII-4 as the experimental group which used the Discovery Learning model assisted by video. The research instrument was a multiple-choice written test. The data collected were analyzed using a normality test, a homogeneity test, and a hypothesis test. Based on the results of the hypothesis test, there was a significant difference in the average scores between the control and experimental classes. This is evidenced by the t-test results, where tcount=2.776 > ttable=2.004. Therefore, H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that the application of Discovery Learning model assisted by video has a significant effect on students' learning outcomes.